Transformasi Kurikulum Pesantren Melalui Metode Pembelajaran Kitab Kuning Dalam Mengembangkan Pesantren : Studi Kasus Di Pondok Pesantren Al-Hikam Malang - Dian Mohammd Hakim (ANDRAGOGI, 2019)
Islamic dorm was the oldest institution in Indonesia. Besides, it’s also a part of macro society. As a part of macro society, it needs to be sustained. One of the important part of Islamic dorm is its curriculum and teaching’s method of classic book. Thus, it is a must to transform both of curriculum and teaching’s method in order to be sustainability in the middle of changing society. The aim of the study is to investigate how curriculum of Al-Hikam transformed to be sustained and how is the teaching’s method of classic book done by Al-Hikam through its transformation. The transformational shape are focused on the area related to the construction of curriculum. As well as matters relating with approach, media, and the method used in the field of teaching and learning process. While, the research of the study done by using qualitative approach. Data collected by using depth interviews, participant observation and documentation. Then, the method of analyzing data used Miles and Hubberman method. The result indicates that there was some transformations of curriculum used at Al-Hikam Malang and some methods used in the teaching process of classic books. Even though, transformation happened, Islamic dorm is still holds on its jargon ‘Al-Muhafadzotu ‘ala qadim al-sholih wa al- akhdu bi al-jadid al-ashlah (Keep on its old tradition which is good and take the new one which is better).Keyword: Transformation, Curriculum, Teaching’s method of classic book.